2020
DOI: 10.3390/en13246545
|View full text |Cite
|
Sign up to set email alerts
|

The Linkages between Crude Oil and Food Prices

Abstract: This paper aims to indicate the linkages between crude oil prices and selected food price indexes (dairy, meat, oils, cereals, and sugar) and provide an empirical specification of the direction of the impact. This paper reviews the fuel–food price linkage models with consideration to the time series literature. This study adopts several methods, namely the Augmented Dickey–Fuller test, Granger causality test, the cointegration test, the vector autoregression model, and the vector error correction model, for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 45 publications
(59 reference statements)
2
22
0
Order By: Relevance
“…In the non-energy sector, the prices of metal commodities such as copper and iron ore are closely related to the Brent Crude oil price, but they cannot be used as auxiliary investing tools due to the low r xy in price change rate. Moreover, we conclude that a weak or moderate price relationship exists between Brent Crude oil and agro-commodities, which supports the finding of several papers [28].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the non-energy sector, the prices of metal commodities such as copper and iron ore are closely related to the Brent Crude oil price, but they cannot be used as auxiliary investing tools due to the low r xy in price change rate. Moreover, we conclude that a weak or moderate price relationship exists between Brent Crude oil and agro-commodities, which supports the finding of several papers [28].…”
Section: Discussionsupporting
confidence: 90%
“…Kousik et al (2020) stated it is still uncertain whether oil prices have relationships with agro-commodity prices [27]. Roman et al (2020) indicated that there are long-term relationships between crude oil and meat prices. The linkage of crude oil prices occurred with food, cereal, and oil prices has been observed in the short term [28].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(Food and Agricultural Orgnaization of United Nations) Literature Review There are few studies which focus on the relationships between sub-indices of food commodity prices. Roman et al (2020) study the relationships between crude oil and food indices. (Dairy, meat, oils, cereals and sugar) They apply cointegration, Vector Auto Regression (VAR) model and Granger causality techniques.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Although the need for causal justification of the indirect effects of biofuels has been recognized, most of the existing causal analyses focus on interactions among biofuel prices, agricultural prices, oil prices and other commodity prices [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. These studies have generally found a strong causal relationship running from crude oil prices to agricultural prices but a tenuous or non-existing causal relationship in the other direction [10,13,16].…”
Section: Introductionmentioning
confidence: 99%